PENANGGULANGAN TRAUMA PADA ANAK-ANAK KORBAN GEMPA BUMI - Safitri Sri Handayani; Lupma Miftah Ul Izza Aziz; Zahra Hafizha Fitria Anam (Journal Medical Universitas muhammadiyah Makassar, 2019)
The earthquake is one of the natural disasters that should be watched out for. The impact of the disaster was not only a material loss but also a loss of life. The most vulnerable earthquake victims are infants, toddlers, and children. This is because of their weak and bad protection abilities. What is caused by the main earthquake is physical trauma and psychological trauma to the victim. Trauma has a more fatal effect on child victims. The need for special actions to handle it.